RIFM fragrance ingredient safety assessment, (2E, 6Z)-Nona-2, 6-dien-1-ol, CAS registry number 28069-72-9. (October 2015) - Api, A.M.; Belsito, D.; Bhatia, S.; Bruze, M.; Calow, P.; Dagli, M.L.; Dekant, W.; Fryer, A.D.; Kromidas, L.; La Cava, S.; Lalko, J.F.; Lapczynski, A.; et al.
Highlights: (2E, 6Z)-nona-2, 6-dien-1-ol safety assessment based on RIFM's criteria. Safety assessment based on 7 Human health endpoints plus environmental. Repeated dose toxicity was determined to be below the TTC. A systemic exposure below the TTC value is acceptable.